Redefining IL11 as a regeneration-limiting hepatotoxin and therapeutic target in acetaminophen-induced liver injury - Widjaja, Anissa A; Dong, Jinrui; Adami, Eleonora; Viswanathan, Sivakumar; Ng, Benjamin; Pakkiri, Leroy S; Chothani, Sonia P; Singh, Brijesh K; Lim, Wei Wen; Zhou, Jin; Shekeran, Shamini G; Tan, Jessie; et al. (Science translational medicine, 2021)
Acetaminophen ( -acetyl- -aminophenol; APAP) toxicity is a common cause of liver damage. In the mouse model of APAP-induced liver injury (AILI), interleukin 11 (IL11) is highly up-regulated and administration of recombinant human IL11 (rhIL11) has been shown to be protective. Here, we demonstrate that the beneficial effect of rhIL11 in the mouse model of AILI is due to its inhibition of endogenous mouse IL11 activity. Our results show that species-matched IL11 behaves like a hepatotoxin. IL11 secreted from APAP-damaged human and mouse hepatocytes triggered an autocrine loop of NADPH oxidase 4 (NOX4)-dependent cell death, which occurred downstream of APAP-initiated mitochondrial dysfunction. Hepatocyte-specific deletion of ( ) in adult mice protected against AILI despite normal APAP metabolism and glutathione (GSH) depletion. Mice with germline deletion of were also protected from AILI, and deletion of or was associated with reduced c-Jun N-terminal kinase (JNK) and extracellular signal-regulated kinase (ERK) activation and quickly restored GSH concentrations. Administration of a neutralizing IL11RA antibody reduced AILI in mice across genetic backgrounds and promoted survival when administered up to 10 hours after APAP. Inhibition of IL11 signaling was associated with the up-regulation of markers of liver regenerations: cyclins and proliferating cell nuclear antigen (PCNA) as well as with phosphorylation of retinoblastoma protein (RB) 24 hours after AILI. Our data suggest that species-matched IL11 is a hepatotoxin and that IL11 signaling might be an effective therapeutic target for APAP-induced liver damage.